An Undescribed Species of Brassaiopsis Decne. et Planch. (Araliaceae) from Andamans - Banerjee, R. N. (Indian Forester, 1968)
Brassaiopsis andamanica R.N. Ban. Spec. nov. (Araliaceae) collected from Black Creek, S. Andamans,is described with illustrations.